2009
DOI: 10.1002/jsfa.3522
|View full text |Cite
|
Sign up to set email alerts
|

Application of polymerase chain reaction–restriction fragment length polymorphism analysis and lab‐on‐a‐chip capillary electrophoresis for the specific identification of game and domestic meats

Abstract: BACKGROUND: The objective of this studywas to adapt and improve previously published polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) methods aimed at the identification of game and domestic meats, by replacing the gel electrophoretic steps for DNA fragment analysis by a chip-based capillary electrophoresis system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Therefore, this study revealed the significant role that PCR-based techniques can play in species identification, and emphasizes the importance of choosing the right genes with suitable variation rates (Brown, 1983;Wolf et al, 1999). This method was successfully used to type both Malaysian wild and domestic cattle, and has previously been used in species identification of game and domestic meats (Prado et al, 2007;Fajardo et al, 2009;Wang et al, 2010;Chen et al, 2010).…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, this study revealed the significant role that PCR-based techniques can play in species identification, and emphasizes the importance of choosing the right genes with suitable variation rates (Brown, 1983;Wolf et al, 1999). This method was successfully used to type both Malaysian wild and domestic cattle, and has previously been used in species identification of game and domestic meats (Prado et al, 2007;Fajardo et al, 2009;Wang et al, 2010;Chen et al, 2010).…”
Section: Discussionmentioning
confidence: 92%
“…Table 14.2 summarizes the most relevant information from reported PCR-RFLP methods, from which it can be inferred that mtDNA markers are mostly targeted to differentiate domestic and game meat species. Most PCR-RFLP methods use gel More recently, chip-based capillary electrophoresis has emerged as an alternative to conventional electrophoresis for RFLP analysis for meat authentication, producing higher resolution band patterns, shorter analysis times, higher versatility, reproducibility, and suitability for automation (Ali et al, 2012a(Ali et al, , 2015aFajardo et al, 2009a;Rahman et al, 2015). …”
Section: Dna-based Methodsmentioning
confidence: 99%
“…Using primers targeting a conserved region in the 12S rRNA gene, followed by restriction enzyme treatment and electrophoretic separation, closely related poultry species could be differentiated (Saini et al, 2007). A similar approach has been used to differentiate game animals such as roe deer, red deer and mouflon from domesticated ruminants (Fajardo et al, 319 2006;Fajardo et al, 2009). Use of a single restriction enzyme may be sufficient for species differentiation by PCR-RFLP .…”
Section: Fig 3 Pcr-rflp For Genotyping -360c/g In the Gene Encodingmentioning
confidence: 99%